(untitled) (Journal of Mathematics Mechanics and Computer Science, 2014)
В статье исследуются вопросы существования, единственности решения линейной нелокальной краевой задачи для систем нагруженных гиперболических уравнений и построения ее приближенных решений. Нелокальная краевая задача для систем нагруженных гиперболических уравнений сводится к эквивалентной задаче, состоящей из семейства двухточечных краевых задач для систем нагруженных обыкновенных дифференциальных уравнений и функциональных соотношений. Семейство двухточечных краевых задач для систем нагруженных обыкновенных дифференциальных уравнений исследуется методом параметризации с неравномерным разбиением интервала между точками нагружения. Для этой цели осуществляется переход к эквивалентному семейству многоточечных краевых задач с функциональными параметрами. Функциональные параметры вводятся как значения неизвестной функции v(x, t) на линиях разбиения. Предлагается алгоритм нахождения решения семейства краевых задач с функциональными параметрами. Основным условием осуществимости и сходимости алгоритма является обратимость матрицы Q(a, x) специальной структуры, построенной по матрицам Aj(x, t), j = 0,m + 1, P2(x), S2(x), (x, t) ∈ Ω, и с учетом поведения матрицы A0(x, t) между точками нагружения. Неизвестные функции определяются с помощью рекуррентных формул нахождения приближенных решений задач Коши. Questions of existence, uniqueness of the solution of linear nonlocal boundary value problem for systems of loaded hyperbolic equations and constructing of its approximate solutions are investigated in the article. Nonlocal boundary value problem for systems of loaded hyperbolic equations is reduced to the equivalent problem, consisting of a family of two-point boundary value problems for systems of loaded ordinary dierential equations and functional relations. The family of two-point boundary value problems for systems of loaded ordinary dierential equations is investigated by parametrization method with nonuniform partition of interval between points of load. For this purpose transition to equivalent family of multipoint boundary value problems with functional parameters is carried out. Functional parameters are entered as values of unknown function v(x, t) on the lines of partition. The algorithm for nding of solutions of the family of boundary value problems with functional parameters is oered. The main condition of feasibility and convergence of algorithm is invertibility of matrix Q(a, x) of the special structure constructed by matrices Aj(x, t), j = 0,m + 1, P2(x), S2(x), (x, t) ∈ Ω, and taking into account behavior of matrix A0(x, t) between points of load. Unknown functions are dened by the recurrent formulas for nding of approximate solutions of Cauchy problem.